Effects of white matter microstructure on phase and susceptibility maps - Wharton, Samuel; Bowtell, Richard W. (Wiley, 2015)
Purpose: To investigate the effects on quantitative susceptibility mapping (QSM) and susceptibility tensor imaging (STI) of the frequency variation produced by the microstructure of white matter (WM).